Introduction to theory of control in organizations. (2015) - Burkov, V. N (Vladimir Nikolaevich), 1939-; Goubko, Mikhail; Korgin, N. A (Nikolaĭ Andreevich); Novikov, D. A (Dmitriĭ Aleksandrovich), 1970-
No abstract available